Penerapan teknik cynema therapy untuk meningkatkan pemahaman siswa terhadap bahaya merokok - Muhammad Fatchurahman (Program Studi bimbingan Konseling PPs UNM Makassar, 2017)
The purpose of the study is to know the application of cinema therapy techniques that can improve students' understanding to the dangers of smoking at SMP Muhammadiyah Palangkaraya. This research is a quantitative experimental approach. Experimental design used in this study was pre-experimental design in the form of one group pretest-posttest design. This means that by this study design uses only one group as the experimental group was given treatment without a comparison group. The population of this study amounted 28 people, with 8 samples indicated the learners who have an understanding to dangers of smoking are low. The collection of research data using interviews, documentation, questionnaires and focus group focus. Analysis of data using statistical test of Paired Samples T Test with application software SPSS version 17.00. The results showed that the cinema therapy techniques can improve students' understanding to the dangers of smoking at SMP Muhammadiyah Palangkaraya.